Haidilao’s Oversea Expansion Research and Analysis – Example from Thailand - Zhang, Buzhi; Bi, Chuanchen (Technium Social Sciences Journal, 2022)
Haidilao was founded in Jianyang Sichuan, in 1994. After 28 years’ development, Haidilao has become a great-renowned and industrial leading hot pot brand. Adhering to the culture of "people-oriented", Haidilao has developed its own business system. Until June 30, 2022, Haidilao has opened 1,435 directly operated stores worldwide. This paper is going to take the overseas strategy of Haidilao in Thailand as an example to analyze the overseas market of Haidilao through literature survey, case analysis and SWOT analysis, hoping the paper can contribute its own effort to the dissemination and sustainable development of Haidilao in Chinese food culture.